C++ 17 standard library quick reference : a pocket guide to data structures, algorithms, and functions - Weert, Peter van; Gregoire, Marc (Software engineer) (Apress, 2019)
This new edition is updated to include all Standard Library changes in C++17, including the new vocabulary types std::string_view, any, optional, and variant; parallel algorithms; the file system library; specialized mathematical functions; and more.